2023
DOI: 10.1002/smll.202207754
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Transformation Strategy Toward Vanadium Dioxide Cathode For Advanced Aqueous Zinc Batteries

Abstract: In the lithium‐dominated era, rechargeable Zn batteries are emerging as a competitive alternative. However, the sluggish kinetics of ion diffusion and structural destruction of cathode materials have thus far hampered the realization of future large‐scale energy storage. Herein, an in situ self‐transformation approach is reported to electrochemically boost the activity of a high‐temperature, argon‐treated VO2 (AVO) microsphere for effective Zn ion storage. The presynthesized AVO with hierarchical structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…47 Comparison with pure VO 2 showed that the peaks of MnVO had shifted, indicating that the introduction of Mn 2+ as a pillar into the tunnel structure of VO 2 altered the main skeleton structure. 48 Figure 3b shows the electron paramagnetic resonance (EPR) spectra of MnVO and VO 2 , providing direct evidence for anionic vacancies.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…47 Comparison with pure VO 2 showed that the peaks of MnVO had shifted, indicating that the introduction of Mn 2+ as a pillar into the tunnel structure of VO 2 altered the main skeleton structure. 48 Figure 3b shows the electron paramagnetic resonance (EPR) spectra of MnVO and VO 2 , providing direct evidence for anionic vacancies.…”
Section: Resultsmentioning
confidence: 96%
“…The peaks at 505 and 683 cm –1 were assigned to the coordination of vanadium atoms with two (V 2 –O) and three (V 3 –O) oxygen atoms, respectively, while the peak at 983 cm –1 corresponded to the stretching vibration of vanadium and terminal oxygen . Comparison with pure VO 2 showed that the peaks of MnVO had shifted, indicating that the introduction of Mn 2+ as a pillar into the tunnel structure of VO 2 altered the main skeleton structure Figure b shows the electron paramagnetic resonance (EPR) spectra of MnVO and VO 2 , providing direct evidence for anionic vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…And, this new phase acts as the subsequent host material to store charge ion. Recently, Deng et al [ 17 ] found that the argon‐treated VO 2 can induce self‐phase transformation into V 2 O 5 ·nH 2 O as new cathode material at the initial charge process by the electrochemical oxidation and water insertion ( Figure a). This resulting V 2 O 5 ·nH 2 O has higher theoretical specific capacity and a self‐adaptive layer transformation structure connected by van der Waals forces for the enhanced significantly specific capacity and cycle stability.…”
Section: Crystal Structure and Zn2+ Ion Storage Mechanism Of Vo2mentioning
confidence: 99%
“…Similarly, Deng et al, Chen et al, and Li et al also found this phase transmission from the initial VO 2 into V 2 O 5 •nH 2 O delivers outstanding performance. [11,17,18] Moreover, this phase transition product may also be zinc vanadate compounds (such as Zn 3 (OH) 2 V 2 O 7 •2H 2 O, Zn 2 V 2 O 7 and Zn 0.25 V 2 O 5 •nH 2 O, Figure 3b-d) as cathode material to storage charge ions for AZMB with superior performance based on the VO 2 and inserted zinc ions reacting with the electrolyte during the initial cycling process. [19] However, the detailed transformation mechanism of this phase transition reaction needs further detailed discussion, such as the transition condition.…”
Section: Diffusion-controlled Faradaic Processmentioning
confidence: 99%
See 1 more Smart Citation